Ecological studies of Asian citrus psyllid Diaphorina citri Kuwayama (hemiptera: psyllidae) and its parasitoid Tamarixia radiata Waterston (hymenoptera: eulophidae) on citrus in Malaysia - Sule, Hassan (2013)
Production of citrus worldwide is being threatened by an invasive pest Diaphorina citri Kuwayama, (Asian citrus psyllid) which is regarded as the most important and efficient vector of bacterium, Liberobacter asiaticum that causes citrus greening disease. The prime concern in increasing production of all citrus fruits is the obstacles posed by the invasive psyllid,D. citri, and lack of sufficient understanding of its population parameters and dynamic, which are essential for development of reliable prediction system and management strategies. The present study was conducted with the objectives of establishing life table and demographic parameters of D. citri, its seasonal fluctuations and dispersion, feeding, oviposition behaviour,parasitism rate and nymphal preference of Tamarixia radiata. Life table studies, choice and no choice assays and parasitism studies were conducted at the insectary of Universiti Putra Malaysia. While population sampling was carried out at Padang Ipoh, Ulu Terengganu, Malaysia. The result of the life table studies showed that, highest mortality in first instar nymphs (40.23%) with k-value of 0.22 and (25.59%) mortality in 2nd instar nymphs with k-value of 0.13 are the key mortality factors regulating the population size. The intrinsic rate of natural increase (rm) was 0.026 per female per day and daily finite rate of increase was 1.023 per female per day,with a mean generation time of 26.53 days. The net reproductive rate of the population was 2.004 and the population doubling time was 26.46 days. The results of choice and no choice assays showed significant number of adult,D. citri were attracted to plants with young flush leaves for oviposition and feeding. When two host plants were assayed together in Y-tube olfactormeter, significantly more number of the adults selected Y-tube arm with Citrus suhuiensis leaves than Y tube arm with Murraya paniculata leaves. Likewisewhen the main pure compounds of the two plants were assayed together in olfactometer, significantly more number of adult D. citri were attracted to β-pinene and β-linalool (main compounds ofC. suhuiensis ) than tocaryophyllene (main compounds ofM. paniculata). Population sampling data revealed that, D. citriadultsin the study area, had fourapparent population peaks appearing in months of March and June, 2011 and Febuary - March and June, 2012. While, D. citri immatures had two apparent population peaks appearing and in the months of July, 2011 and March, 2012. Furthermore, population of D. citriadultswere found to be more abundant on the upper canopy, leaf growth stage 1 and northern cardinal point. The Correlation analysis showed that population of D. citriadultswas strongly correlated with number of flush leaves (r = 0.93) and modaretly correleted with temperature (r = 0.45), while population of immatures was only correlated with flush leaves. However, the stepwise regression analysis between the observed population and the environmental parameters showed that only flush leaves contributed to the build up/ fluctuation of D. citri population.Spatial distribution pattern analysis of the psyllid on C. suhiensis using various indices of population dispersion and regression models showed an aggregated distribution. Parasitism study revealed that, significantly more number of 5th and 4th instars nymph were parasitized by adult,T. radiata compared to the remaining nymphal stages. Similarly, when 3rd, 4th and 5th instars nymphs were assayed in choice experiment, significantly more number of older nymphs were parasitized by adult,T.radiata. Furthermore, functional responses of T. radiata to different densities of 3rd,4th and 5th instars nymphs of D. citrishoweda type II functional response, with 1.11,0.60 and 0.71 handling time, and 21.62, 39.99 and 34.04 attack rate,respectively. Therefore, based on results obtained in this study, β-pinene and β-linalool could be use for monitoring and trapping of D. citri. Monitoring should be initiated when plants have started to produce flush leaves and continue until the end of the flushing season and monitoring interval could be weekly or every 10 days on at least 35 trees in every 1.5 hectare plot. When control measure is required, it should be done on tree by tree basis since D. citri showed aggregated distribution and effort should be concentrated on the upper canopies of the trees.